Sultan Muhammad Mulia Ibrahim Syafiuddin in Islamic civilization at Sambas 1931-1943: restructuring of Islam government and infrastructure development - Posha, Beti Yanuri (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2024)
The Islamic Kingdom of Sambas, known as Sambas Sultanate, was established on 10 Zulhijjah 1040 /10 July 1631. Sambas Sultanate was famous since the first Sambas Sultan, Sultan Muhammad Syafiuddin I (1631-1668), until the 15th Sultan of Sambas Sultan Muhammad Mulia Ibrahim Syafiuddin (1931-1943). The purpose of this article is to review how the influence of Sultan Muhammad Mulia Ibrahim Syafiuddin in 1931-1943 on the progress of contemporary Islamic civilization in Sambas area. This study uses historical method with steps: heuristics, verification, interpretation and historiography. The results showed that the influence of the Sultan was restructuring the Islamic government through aspects of renewing educational institutions, religious institutions, politics, and Islamic law. At the same time, infrastructure development, such as many major roads were expanded by the Sultan and even built two large bridges as a means of transportation for the people of Sambas which are used until now, as well as in the field of architecture renovating the palace and making the symbol of the Alwatzikubillah palace.